The Variants at APOA1 and APOA4 Contribute to the Susceptibility of Schizophrenia With Inhibiting mRNA Expression in Peripheral Blood Leukocytes - Fan, Yao; Gao, Jun; Li, Yinghui; Chen, Xuefei; Zhang, Ting; You, Weiyan; Xue, Yong; Shen, Chong (Frontiers in Molecular Biosciences, 2021)
Objective: Abnormal lipid metabolism has a close link to the pathophysiology of schizophrenia (SZ). This study mainly aimed to evaluate the association of variants at apolipoprotein A1 (APOA1) and APOA4 with SZ in a Chinese Han population. Methods: The rs5072 of APOA1 and rs1268354 of APOA4 were examined in a case–control study involving 2,680 patients with SZ from the hospital and 2,223 healthy controls screened by physical examination from the community population. The association was estimated with the odds ratio (OR) and 95% confidence intervals (95% CIs) by logistic regression. The APOA1 and APOA4 messenger RNA (mRNA) in peripheral blood leukocytes were measured by real-time PCR and compared between SZ cases and controls. Serum apoA1 levels were detected by turbidimetric inhibition immunoassay and high-density lipoprotein cholesterol (HDL-C) levels were detected by the homogeneous method. Results: Both of the rs5072 of APOA1 and rs1268354 of APOA4 had statistically significant associations with SZ. After adjustment for age and sex, ORs (95% CIs) of the additive model of rs5072 and rs1268354 were 0.82 (0.75–0.90) and 1.120 (1.03–1.23), and p-values were 3.22 × 10−5 and 0.011, respectively. The association of rs5072 with SZ still presented statistical significance even after Bonferroni correction (p-value×6). SZ patients during the episode presented lower levels of apoA1, HDL-C, mRNA of APOA1 common variants and transcript variant 4, and APOA4 mRNA than controls (p < 0.01) while SZ patients in remission showed a significantly decreased APOA1 transcript variant 3 expression level and increased APOA4 mRNA expression level (p < 0.01). mRNA expression levels of APOA1 transcript variant 4 significantly increased with the variations of rs5072 in SZ during the episode (ptrend = 0.017). After the SZ patients received an average of 27.50 ± 9.90 days of antipsychotic treatment, the median (interquartile) of serum apoA1 in the SZ episode significantly increased from 1.03 (1.00.1.20) g/L to 1.08 (1.00.1.22) g/L with the p-value of 0.044. Conclusion: Our findings suggest that the genetic variations of APOA1 rs5072 and APOA4 rs1268354 contribute to the susceptibility of SZ, and the expression levels of APOA1 and APOA4 mRNA of peripheral blood leukocytes decreased in SZ patients during the episode while APOA4 increased after antipsychotic treatment.